Pengaruh Terapi Bermain Paper toys terhadap Peningkatan Perkembangan Motorik Halus pada Anak dengan Retardasi Mental - Andini Rahma Diyanti; Riska Wati; Retno Anggraeni Puspita Sari; Previarsi Rahayu (Jurnal Keperawatan Florence Nightingale, 2025)
Children with mental retardation commonly experience developmental delays, including impairments in fine motor skills that play a crucial role in academic readiness and daily functional independence. The limited use of engaging and structured interventions in special education settings often results in suboptimal fine motor stimulation. This study aimed to analyze the effect of paper toy play therapy on improving fine motor development in children with mental retardation. A pre-experimental one-group pretest–posttest design was employed involving 37 students at SDLB Ananda Mandiri Tambun, Bekasi Regency. Fine motor development was assessed using a 12-item observational checklist administered before and after four intervention sessions. The findings showed an increase in the mean score from 20.16 to 26.43. The Wilcoxon Signed-Rank test yielded a p-value < 0.001, indicating a statistically significant difference between pretest and posttest scores. Before the intervention, most children were categorized as poor or adequate; however, post-intervention assessments demonstrated an increase in the number of children who achieved good fine motor performance. This study concludes that paper toy play therapy is effective in enhancing fine motor skills in children with mental retardation. Its implications highlight the potential for integrating this therapy into individualized education programs in sp